Adaptive Capacity Level Shapes Social Vulnerability to Climate Change of Fishing Communities in the South Brazil Bight - Martins, Ivan Machado; Gasalla, Maria A. (Frontiers in Marine Science, 2020)
Understanding the social vulnerabilities and community strategies to adapt to environmental changes is crucial for the development of actions to enhance community conservation and survival. With the aim to identify the drivers of vulnerability to climate change among different coastal communities across a large marine ecosystem, a comprehensive multi-scale vulnerability framework was here adopted. Eight selected fishing communities representative of the South Brazil Bight were surveyed at the household level. A total of 151 fishers were interviewed. Findings revealed a series of adaptation patterns evidencing that remoteness and the lack of climate change-related institutional support increase vulnerability among fishing villages. On the other hand, community organization, occurrence of strong leadership, partnerships with research activities, community-based co-management and livelihood diversification reduce vulnerability. Our analysis focused on social vulnerability to climate change in regional fishing communities and provides a better understanding of these effects in coastal zones, the factors explaining vulnerability and some perspectives on resilient and adaptable systems. Learning from comparisons at the ecosystem level may be applied to coastal regions elsewhere.